SCIENTIFIC RESEARCH OF HIGHER EDUCATION APPLICANTS IN THE CONTEXT OF TRENDS IN THE DEVELOPMENT OF LEGAL SCIENCE - Sopilko, Iryna; Cherevatiuk, Victoria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose of the scientific paper is to summarize the results of the VIІ International Youth Scientific Legal Forum in the context of the relationship between scientific research of higher education applicants and the development trends of modern legal science. Research methods: to achieve the objective stated, general and special scientific (special) methods were used, in particular, formal-legal, comparative-legal, logical-legal methods, and the like. The application of these methods allows us to analyze the trends in the development of legal science in modern conditions and find out how the scientific research of higher education applicants correlates with them. Results: modern conditions dictate the need for constant improvement of legal scientific developments, which is only possible if higher education applicants develop different levels of relevant research skills, which must be acquired while studying at a higher education institution, attending problem, binary, and other types of lectures, preparing scientific works and research projects, reports and speeches at conferences and other scientific events, analyzing legislation in the process of studying academic subjects, during internships, traineeships and the like. The art of discovery in science, the ability to analyze information from different sources combined with critical thinking, make informed decisions, and draw conclusions based on a deep understanding of the subject of research can all be acquired and developed during training. When starting their scientific activity, applicants for higher education of the specialty 081 Law should pay attention to the choice of a topic that meets the development trends of modern legal science. Discussion: modern legal science is characterized by dynamic and multidimensional approaches to the understanding and application of law. They include various trends and methodologies to solve modern issues and use new technologies. Analyzing the relationship between the choice of subjects for scientific research of applicants for higher education on the specialty 081 Law together with the general trends in the development of modern legal science, we can summarize that in the overwhelming majority, the speeches and abstracts of the VIІ International Youth Scientific Legal Forum participants are relevant and fully consistent with these trends. Naturally, the topics of scientific research of the forum participants were influenced by Russian military aggression and the introduction of martial law in Ukraine and related issues, in particular, restrictions on human rights, protection of children’s rights, protection of the rights of military personnel and prisoners of war, internally displaced persons, and the like.